Transformational Leadership, Organizational Culture and Organizational Commitment in Forming Performance in Secretariat Employees DPRD Surakarta - Suprayitno, Yuneth Tahapary, Marjam Desma Rahadhini & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Human resource management is one of the functions of the organization, and whenthe function is running well, the organization is expected to strive for employees toprovide optimal performance in accordance with the expected. Factors that mayaffect employee performance are transformational leadership, organizationalculture and organizational commitment. Transformational leadership is a state inwhich employees feel trust, admiration, loyalty, and respect for their leaders.Organizational culture is the norm, belief, attitude and philosophy that embracedsomeone in achieving organizational goals. Organizational commitment is apsychological state that characterizes the relationship of employees with theorganization and that affects employees will remain in the organization or not. Theobject of this research is Secretariat Staff of DPRD Surakarta. Based on presurveyin Secretariat DPRD Surakarta has a phenomenon of human resources problems,namely: the leader can not be a good example for employees, there are leaders whooften come late, not obey the rules set. Employees have difficulty completing taskson time, so the job becomes ineffective. Employees are also less confident aboutthe organization, because of the lack of rewards for employees who have goodperformance.Keywords: transformational leadership, organizational culture, commitment organization,employee performance